Influence of stress factors on the state of the human body and organs and tissues of the oral cavity (literature review) - Verbenets Х. В.; Furdychko А. І.; Fedun І. Р.; Riznyk Ю. Б. (Actual Dentistry, 2024)
Abstracts. In today’s environment, every citizen of Ukraine is exposed to varying degrees of psycho-emotional and physical stress. It is impossible to underestimate the negative impact of stressors on the tissues and organs of the oral cavity in particular, as quite often the first signs of general pathologies appear in this complex. The aim of the study is to analyse data from scientific literature sources and provide updated information on the impact of psycho-emotional stress on the development of periodontal diseases in the current conditions. Materials and Methods. The bibliosemantic method was used to clarify the state of the problem, to study the analysis of the results of previous scientific research based on the sources of literature and electronic resources. Research results and discussion. The current conditions dictated by the war on the territory of our country is cause a state of permanent stress among the population of Ukraine, which is related to the basic human instinct of survival. In general, a person can be affected by one or more groups of objective causes of stress. The citizens of Ukraine are experiencing severe stress as a result of the ongoing conflict. This includes combatants, relatives and friends of these combatants, civilians living in the area close to the hostilities, the wounded, medical workers, and internally displaced persons. The stress factor provokes the emergence and rapid development of new mental and somatic diseases, it leads to the progression of existing diseases, but the reaction to the stimulus is different for each person and is an individual manifestation. The state of the oral cavity is a very sensitive complex to any changes in the body’s homeostasis, and often the first signs of general pathologies appear in it. Among the significant risk factors that contribute to the development and aggravate the course of periodontal disease, stress is one of the most important. Long-term exposure to stress can suppress the acquired immune response, causing an imbalance between pro-inflammatory and anti inflammatory factors. Experimental studies in rat glands have demonstrated that acute stress induces dystrophic and necrobiotic changes in the gland, resulting in a reduction in its protein synthesis function. Psychological stress can contribute to disruption of the usual lifestyle, which adversely affects hygiene. Conclusions. After analysing scientific research data and reports on the current state of psycho-somatic health of people in Ukraine in modern realities, it is obvious that the prevalence and intensity of periodontal tissue diseases may have a new negative development. The peculiarities of the development, prevention and treatment of periodontal diseases in people experiencing severe psycho-emotional and sometimes physical stress require additional study and analysis.